Accelerometers Provide Early Genetic Selection Criteria for Jumping Horses - Ricard, Anne; Dumont Saint Priest, Bernard; Danvy, Sophie; Barrey, Eric (Frontiers in Genetics, 2020)
The aim of this study was to evaluate the genetic component of the locomotor jumping ability via a wearable accelerometer sensor and to estimate the genetic correlation with the performances in competition in order to introduce such criteria in selection schema. A sample of 1056 young 3 years old horses were equipped with a 3-dimension accelerometer during free jumping test in regular breeding shows from 2015 to 2017. Seven variables were extracted from the dorso ventral acceleration curve for the last 3 jumps over a double bar obstacle of 1.15 m for the front pole and 1.20 m for the back pole with 1.20 m spread. Variables were the peaks of forelimbs, hind limbs and landing acceleration, the duration between peaks at take-off, peak of forelimbs acceleration and start of jump, jump duration and duration between the beginning of the impact of forelimbs and the peak at the landing. During breeding show, judges scored balance, strength, style and reactivity for free jumping and jumping test under saddle. Jumping competition results were recorded by logarithm of sum of points earned in each competition. All horses in official competition were included, i.e. 160,257 horses born from 1997 and 649,491 annual performances. An animal mixed model with complete pedigree over 4 generations (353,236 horses) were used with fixed effect of jumping test location and date, morning/afternoon, gender, month of birth, rank of jump for accelerometric data, effect of year of competition combined with age and gender for competition results. As results, jump duration was the most heritable and repeatable over jumps variable: h2=0.16 (0.06), r=0.52 (0.02). Accelerations were moderately heritable (h2=0.05 to 0.09, r=0.39 to 0.51). Judges scores were heritable: 0.21 (0.07) to 0.33 (0.09) and highly correlated. Scores during free jumping were genetically correlated to jump duration: 0.71 (0.15) to 0.88 (0.16). Both jump duration and judges scores were genetically correlated to competition performance: 0.59 (0.13) for jump duration, from 0.60 (0.11) to 0.77 (0.12) for scores. Jump duration and judges scores can be used as early selection criteria. The advantage of the accelerometric measurement is its objectivity and ease of recording.